Kaitan Tingkat Intensitas Bunyi terhadap Jarak dari Mesin Pembangkit Listrik (Genset) di RSUD Dayaku Raja Kota Bangun - melti lestiyani lestiyani; Suhadi Muliyono; Devina Rayzy Perwitasari Sutaji Putri (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Research has been carried out on the relationship between the level of sound intensity and the distance on region 1 and region 2 from a power generator set (genset) at the Dayaku Raja Hospital, Kota Bangun. The sound intensity level value (β) is used as the dependent variable and the distance value (d) is used as the independent variable. Measurement distance in region 1 is 7 meters, while in region 2 is 30 meters, where measurement space of β is 1 meter used Sound Level Meter. Furthermore, average of β plotted with the distance (d), which the distance from the outer surface of the gensets house wall to measurement point of β (region 1) and the distance from the inner surface of the halfway house wall to measurement point of β (region 2) which the longer of the distance the smaller β are produced, where the linier curves with negative gradient are produced, that is (-1,6dB/m)d + 71,9dB (region 1) dan β = (-0,2dB/m)d + 50,1dB (region 2). On the research, β is on the range of 60 dB to 70 dB on region 1 and 40 dB to 50 dB on region 2 are produced. Thus, β from a power generator (genset) at the Dayaku Raja Hospital Kota Bangun less than Noise Threshold Value based on Peraturan Menteri Tenaga Kerja dan Transmigrasi No. 13/MEN/X/2011.